TRANSFORMATION OF WORK DISCIPLINE, LEADERSHIP STYLE, AND EMPLOYEES PERFORMANCE BASED ON 21st CENTURY GLOBAL CITIZENS LIMITED COMPANY - Imam Muhtadin; Lili Purnama Sita (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
Muhammadiyah Jakarta of the University, FEB UPI YAI Jkt, ABSTRACTResearch that analyzes transformation work discipline, leadership style, employees performance based on 21st century global citizens limited company. The research was held at the Pratama Abadi Industri Limited Company Jl. Raya Serpong No. KM, Pakualam, Kec. North Serpong, South Tangerang City. The method used is a quantitative survey type with a sample of 70 respondents, the results of the calculation with t count > t table (4.684 > 1.66792) means that this number is significant from the Leadership Style (X 1 ) of 0.009 > 0.05 and here has a positive effect . so for Ho it is said to be rejected and for Ha it is definitely accepted so that the Style Leadership variable (X 1 ) has a clear positive or very significant effect on employee performance in this company. for t count > t table (2,476 > 1,66792) with a significant value of Work Discipline (X 2 ) of 0.000 < 0.05 of course the direction of the coefficient is also positive. So based on this data, Ho is clearly rejected and of course Ha is definitely accepted with the Work Discipline variable (X 2 ) having a very significant positive effect. From the results of the F test calculation above, it can be seen that Fcount > Ftable (19.057 > 3.13) with a significant value of 0.000 less than 0.05, so it can be concluded that Ho is rejected and Ha is accepted, meaning that the two Leadership Style variables (X1) and Work Discipline (X2) together (simultaneously) has a positive and significant effect on the Employee Performance variable (Y) at Limited Company Pratama Abadi Industri